DZIELIMY SIĘ DOŚWIADCZENIEMLarge true left ventricular aneurysm - Bugajski, Paweł; Jarząbek, Radosław; Greberski, Krzysztof; Olszewski, Roman; Jedliński, Ireneusz; Duszyńska, Małgorzata; Wardęga, Tomasz; Kalawski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: Left ventricular aneurysm results most commonly from myocardial infarction. True or false – in many cases is apparent only when surgery is done. Case report: A 61-year-old male was admitted to the hospital due to weakness, exercise tolerance deterioration and increasing dyspnoea. He did not complain of chest pain. TEE examination revealed a false left ventricular aneurysm of the posterior wall containing thrombotic material. Coronarography showed total occlusion of CX and non-critical occlusion of LAD. Aneurysmectomy revealed a huge, true left ventricular aneurysm of the posterior wall, attached to the diaphragm and relocating the heart. Dislocation of heart made ascending aorta cannulation impossible; thus femoral cannulation was performed. The left ventricle was closed by a double layer linear suture and two venous coronary-artery grafts were sewn. Results: The postoperative course was complicated by transient symptoms of confusion and pneumonia. On POD 14 the patient in good overall condition was discharged from the cardiac surgery department. Conclusions: The symptoms of left ventricular aneurysm could be the first symptoms of myocardial infarction. Eventually the surgical procedure revealed a true left ventricular aneurysm that was depicted as a false aneurysm in preoperative evaluation. Uncommon arterial cannulation could improve safety of the surgical procedure.